Burden and mortality of breast cancer attributed to diabetes and smoking in women: a secondary analysis based on Global Burden of Disease 2019 in North Africa and the Middle East - Fatemeh Khosravi Shadmani; Ali Jafari-Khounigh; Leili Abedi Gheshlaghi; Leila Rezakhani; Mozafar Khazaei (BMJ Open)
Background Breast cancer (BC) is the second most common cancer in the world. This study aimed to investigate the burden of BC due to some risk factors in the Middle East and North Africa (MENA) countries from 1990 to 2019.Methods This study is a secondary analysis based on the Global Burden of Disease 2019 data. In this study, we used data for disability-adjusted life years (DALYs) and mortality of BC in MENA countries. Also, we presented data for DALYs and mortality attributed to diabetes, smoking and passive smoking among women with BC.Results The age-standardised DALY due to BC in women increased slowly from 395 (95% CI: 357 to 458) per 100 000 in 1990 to 473 (95% CI: 409 to 544) per 100 000 in 2019. But Kuwait, Bahrain, Jordan and Turkey saw a decrease in age-standardised DALY trends between 1990 and 2019. In 1990, the age-standardised mortality rate was 12.3 (95% CI: 11.0 to 14.2) per 100 000 people, and by 2019, it had increased to 15.2 (95% CI: 13.3 to 17.3) per 100 000. The rate in 2019 varied between countries. Diabetes, smoking and passive smoking contribute significantly to the burden of disease and mortality from BC, with diabetes playing a more impactful role than the other risk factors. Across the MENA region, the burden and mortality attributed to diabetes vary among countries.Conclusion In the MENA region, the attributable fraction of risk factors such as diabetes, smoking and secondary smoking over BC deaths and DALY has increased in recent years.